Tectonic Evolution of the Western Margin of the Burma Microplate Based on New Fossil and Radiometric Age Constraints. Issue 5 (22nd May 2019) - Aitchison, Jonathan C.; Ao, Aliba; Bhowmik, Santanu; Clarke, Geoffrey L.; Ireland, Trevor R.; Kachovich, Sarah; Lokho, Kapesa; Stojanovic, Denis; Roeder, Tara; Truscott, Naomi; Zhen, Yan; Zhou, Renjie
Abstract: Results of biostratigraphic and geochronological investigations in eastern Nagaland and Manipur, NE India, provide new constraints on the tectonic evolution of the western margin of the Burma microplate. U/Pb zircon ages indicate that the Naga Hills ophiolite developed in a suprasubduction zone setting as part of an intraoceanic island arc developed during late Early Cretaceous (mid‐Aptian) time and is younger than similar rocks exposed along the Indus‐Yarlung Tsangpo suture zone. Radiolarian microfossils provide Jurassic and Cretaceous age constraints for Tethyan ocean floor sediments that were subducted beneath the forming ophiolite. Timing of the emplacement of these rocks onto the passive margin of eastern India is constrained by Paleocene/Eocene radiolarians in sediments over which the ophiolitic assemblage has been thrust. Previously undated schists and gneisses in the Naga Metamorphics are of Early Ordovician age, and their sedimentary protolith was most likely derived from sources in the south of Western Australian and East Antarctica. After Barrovian‐style metamorphism, these rocks were uplifted and eroded becoming an important source of detritus shed into the Eocene Phokphur Formation. This unit also contains abundant clasts sourced from the disrupted basement of the Naga Hills ophiolite, which it overlies. It also contains Permo‐Triassic‐aged detritus eroded off an enigmatic source that was possibly a continental convergent margin arc system somewhere along the northern margin of Gondwana. Key Points: Naga Metamorphics are of Early Ordovician age, and their protolith was derived from south Western Australian and/or East Antarctic sources Paleocene/Eocene radiolarians in mélange confirm timing of Naga Hills Ophiolite (Aptian) emplacement onto the east Indian passive margin The Phokphur Formation contains enigmatic Permo‐Triassic detritus possibly from a continental arc on the northern margin of Gondwana